Mixed Method Research on Football Coaches’ Competitive Behavior - Rodrigues, José; Rodrigues, Filipe; Resende, Rui; Espada, Mário; Santos, Fernando (Frontiers in Psychology, 2021)
Objective: The purpose of this study was to display a mix-method type study assessing football coaches’ competitive behavior, considering three instruments, namely the System of Analysis of Instruction in Competition, the Coach Instructional Behavior Expectations Questionnaire, and the Coach Instructional Behavior Perception Questionnaire. Methods: The three instruments underwent a robust process of construction and validation. Inter- and intra-observer reliability was tested for the observational instrument, using Cohen’s k-agreement measure. Reliability values above 0.85 were considered as a good agreement between and within observers. To verify the internal consistency of the questionnaires, the correlation coefficients were considered. Results: The results related to intra-observer and inter-observer reliability showed that intra-observer reliability k-agreement values ranged between .912 and 1 for observer 1, and .82 and 1 for observer 2. For inter-observer reliability, k-agreement values ranged between .885 and 1 between observers. Thus, values for reliability are above acceptable. The correlation coefficient values recorded for the questionnaires on instruction expectations in the competitive moment were above 0.82 and significant (p<0.01), and for the questionnaire on instruction perception in competition above 0.88 and significant (p<0.01). The pilot study showed some divergent results across expectations, behavior in competition, and perception about the instruction behavior. Conclusion: The observational system and the expectations and perceptions questionnaires, used in a complementary way, can be considered for mix-method studies as a mean to examine football coaches’ competitive behavior.